Psikologi Komunikasi dalam Pendidikan Islam - Ceceng Ahmad; Noorchasanah; Bambang Samsul Arifin (STAI Terpadu Yogyakarta, 2021)
Communication psychology is described as a science that seeks to describe, predict, and control mental and behavioral events (behavior) in communication. The educational problem that is often neglected in educational activities is that it does not pay attention to the psychological aspects of interacting between individuals, more precisely on the psychological aspects of communication. Educators and students often experience boredom in study and work, boredom, laziness, and loss of motivation are psychological symptoms that are often approached by people who are studying or working. This symptom to some degree will affect learning and work outcomes. Gives birth to a class crisis, a loss of motivation and a loss of excitement. The research method used in writing this article is descriptive-qualitative. The descriptive-qualitative approach is used to study the psychology of organizational communication in the perspective of Islamic education. The concept of communication psychology in the perspective of Islamic education must be based on a teacher-student relationship that is full of love and affection, love and affection, openness, freedom, honesty, sincerity and sincerity, religion, family atmosphere, and not in an atmosphere of power.